Analysis of the Government's Role in Promoting Innovation Readiness in Micro, Small, and Medium-sized Industries in Indonesia - Muhammad Farid; Aris Baharuddin; Muh. Ihsan Said (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
In the context of Indonesia's evolving economic landscape, this study delves into the critical issue of innovation readiness within its Micro, Small, and Medium-sized Enterprises (MSMEs) sector. Recognizing the significant role of governments in fostering innovation, this research aims to comprehensively analyze the government's contributions to enhancing innovation readiness in Indonesian MSMEs. Employing a qualitative research approach, this study investigates government policies, regulatory frameworks, and collaborative initiatives with industry associations and research institutions. The findings illuminate the effectiveness of these interventions and provide valuable insights for policymakers and stakeholders striving to bolster Indonesia's economic development and competitiveness through innovation support in the MSME sector.